A review of ECG and QT interval measurement use in a public psychiatric inpatient setting. (February 2018) - Berling, Ingrid; Gupta, Rahul; Bjorksten, Cecilia; Prior, Felicity; Whyte, Ian M; Berry, Sherman
Objectives: There is an increased rate of sudden cardiac death (SCD) in mental health patients. Some antipsychotic medications are known to prolong the QT interval, thus increasing a patient's risk of SCD via the arrhythmia, torsades de pointes (TdP). Our aim was to evaluate assessment for QT prolongation within a public inpatient mental health facility by auditing electrocardiograph (ECG) use. Methods: We reviewed records of all mental health inpatient admissions to a public emergency mental health inpatient unit between 1 January 2016 and 11 February 2016. ECG availability was noted and QT interval was manually measured and assessed for risk of TdP using the QT nomogram when present. Demographic information and medication use was collected. Results: Of 263 mental health inpatient admissions, 50 (19%) presentations had an ECG. A total of four (8%) had a prolonged QT interval. Of the 50 patients with an ECG, 12 (24%) were taking medication known to prolong the QT interval. Conclusions: There was very limited risk assessment for QT prolongation in a public hospital psychiatric inpatient unit, with less than 20% of patients having an ECG performed. Our study supports an association between QT-prolonging drugs and a clinically significant prolonged QT interval; however, a larger study with routine ECG screening is required.